The transcription factor Nrf2 links Th2-mediated experimental allergy to food preservatives - Jin, Yining; Boss, Allison P.; Bursley, Jenna K.; Wilson, Caitlin; Gangur, Venugopal; Rockwell, Cheryl E. (Frontiers in Immunology, 2025)
IntroductionImmune-mediated adverse reactions to food allergens are rising at a striking rate, for reasons that are not completely understood. Our previous studies suggest that the stress-activated transcription factor Nrf2 (Nuclear factor erythroid 2 -related factor) promotes Th2 differentiation, while inhibiting Th1 differentiation.MethodsIn the present studies, we investigated the effect of Nrf2 activation on sensitization and anaphylaxis in response to food allergen in BALB/c mice. Specifically, we determined the effect of the Nrf2 activator and common food preservative tBHQ (tert-butylhydroquinone) on immune response to food allergen in Balb/c mice and SCID mice that received either wild-type or Nrf2-deficient CD4 T cells.ResultsOur results demonstrate that tBHQ strongly increases IgE sensitization to ovalbumin (OVA) with a concurrent increase in plasma IgG1 concentrations. In addition, tBHQ in diet also exacerbated anaphylaxis and increased mast cell degranulation. In a recall response, tBHQ promoted a type 2 T cell response. Notably, adoptive transfer studies in SCID recipient mice indicate that Nrf2 expression in CD4+ T cells is critical to sensitization and anaphylaxis in response to food allergen. Likewise, the effects of tBHQ on sensitization and challenge are dependent on Nrf2 expression in CD4+ T cells.ConclusionOverall, these studies point to a key role for Nrf2 in the immune response to food allergen. In addition, this study shows that the common food preservative tBHQ promotes allergic sensitization and anaphylaxis in experimental food allergy.